Impact of weight loss for depressive symptom in mid-stage patients with Parkinson’s disease: a 4-year follow-up study - Kurihara, Kanako; Fujioka, Shinsuke; Mishima, Takayasu; Tsuboi, Yoshio (Frontiers in Neurology, 2024)
10.0 years, mean disease duration was 6.8 ± 4.0 years, and mean Hoehn and Yahr stage was 2.4 ± 0.7. Among them, 48 patients (50.0%) had a weight loss of ≥5% from baseline (weight loss group; mean loss was 6.6±2.9 kg). The weight loss group was older (P = 0.031), had a lower Mini-Mental State Examination (MMSE) at baseline (P = 0.019), and had a significantly lower body mass index (P < 0.001) and higher Zung Self-Rating Depression Scale (SDS) (P = 0.017) at end date. There was a negative correlation (γ = -0.349, P < 0.001) between weight change and age, a positive correlation (γ = 0.308, P = 0.002) between weight change and MMSE at baseline, and a negative correlation (γ = -0.353, P < 0.001) between weight change and SDS at end date. Age-adjusted correlations showed a final negative correlation (γ = -0.331, P = 0.001) between weight change and SDS. MMSE and age adjusted correlations showed a low negative correlation (γ = -0.333, P = 0.001) between weight change and SDS at end date.Weight loss in PwPD in mid-stage was more likely with increasing age, and a ≥5% weight loss was associated with worsening depression. Further research is needed regarding the significance of weight loss in PwPD.